Midgut expression of immune-related genes in Glossina palpalis gambiensis challenged with Trypanosoma brucei gambiense - Hamidou Soumana, Illiassou; Tchicaya, Bernadette; Chuchana, Paul; Geiger, Anne (Frontiers in Microbiology, 2014)
Tsetse flies from the subspecies Glossina morsitans morsitans and Glossina palpalis gambiensis respectively transmit Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense. The former causes the acute form of sleeping sickness, and the latter provokes the chronic form. Although several articles have reported G. m. morsitans gene expression following trypanosome infection, no comparable investigation has been performed for G. p. gambiensis. This report presents results on the differential expression of immune-related genes in G. p. gambiensis challenged with T. b. gambiense. The aim was to characterize transcriptomic events occurring in the tsetse gut during the parasite establishment step, which is the crucial first step in the parasite development cycle within its vector. The selected genes were chosen from those previously shown to be highly expressed in G. m. morsitans, to allow further comparison of gene expression in both Glossina species. Using quantitative PCR, genes were amplified from the dissected midguts of trypanosome-stimulated, infected, non-infected and self-cleared flies at three sampling timepoints (3, 10, and 20 days) after a bloodmeal. At the 3-day sampling point, transferrin transcripts were significantly up-regulated in trypanosome-challenged flies versus flies fed on non-infected mice. In self-cleared flies, serpin-2 and thioredoxin peroxidase-3 transcripts were significantly up-regulated ten days after trypanosome challenge, whereas nitric oxide synthase and chitin-binding protein transcripts were up-regulated after 20 days. Although the expression levels of the other genes were highly variable, the expression of immune-related genes in G. p. gambiensis appears to be a time-dependent process. The possible biological significance of these findings is discussed, and the results are compared with previous reports for G. m. morsitans.